HUBUNGAN STATUS GIZI TERHADAP KEMAMPUAN RENANG GAYA BEBAS MAHASISWA STKIP YPUP MAKASSAR - akbar yusuf; andi sahrul jahrir (UNIVERSITAS NEGERI MAKASSSAR, 2021)
This study aims to obtain answers to problems (1) Is there a significant relationship between height and freestyle swimming ability of STKIP YPUP Makassar students?. (2). Is there a significant relationship between body weight and the freestyle swimming ability of STKIP YPUP Makassar students, (3 Is there a significant relationship between height and weight on the freestyle swimming ability of STKIP YPUP Makassar students?This research is descriptive of two independent variables and one dependent variable. The population and sample are students of STKIP YPUP Makassar selected by random sampling obtained as many as 20 people. The data analysis technique used was single correlation analysis and multiple correlation analysis using computer facilities through the SPSS program.Based on the results of data analysis, it can be concluded as follows: (1) there is a significant relationship between height and the freestyle swimming ability of STKIP YPUP Makassar students with a value of r = 0.813 (P <0.05), (2) there is a significant relationship between body weight and style swimming ability. freestyle STKIP YPUP Makassar students with a value of r = 0.727 (P<0.05), (3) there is a significant relationship between height and weight on the freestyle swimming ability of STKIP YPUP Makassar students with a value of R = 0.754 (P<0.05) (ro) = 0.788 (P<0.05).